2022
DOI: 10.3390/life12020271
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of Glucose-6-Phosphate Dehydrogenase in Tumorigenesis and Cancer Chemoresistance

Abstract: The pentose phosphate pathway (PPP) is a branch from glycolysis that begins from glucose-6-phosphate (G6P) and ends up with fructose-6-phosphate (F6P) and glyceraldehyde-3-phosphate (GADP). Its primary physiological significance is to provide nicotinamide adenine dinucleotide phosphate (NADPH) and nucleotides for vital activities such as reactive oxygen species (ROS) defense and DNA synthesis. Glucose-6-phosphate dehydrogenase (G6PD) is a housekeeping protein with 514 amino acids that is also the rate-limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 111 publications
1
33
0
Order By: Relevance
“…G6PD-deficient individuals are susceptible to the development of favism, neonatal jaundice and infection/drug-induced hemolysis primarily due to oxidative stress [ 30 ]. An increasing body of evidence in the last decade has documented the aberrantly high expression of G6PD in several types of cancers [ 11 , 13 , 15 , 31 ]. Thus, our study was aimed to determine the oncogenic role of G6PD in promoting cellular proliferation, survival and chemotherapeutic drug resistance in MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G6PD-deficient individuals are susceptible to the development of favism, neonatal jaundice and infection/drug-induced hemolysis primarily due to oxidative stress [ 30 ]. An increasing body of evidence in the last decade has documented the aberrantly high expression of G6PD in several types of cancers [ 11 , 13 , 15 , 31 ]. Thus, our study was aimed to determine the oncogenic role of G6PD in promoting cellular proliferation, survival and chemotherapeutic drug resistance in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has demonstrated that G6PD expression is upregulated in several types of cancers and it promotes tumor progression [ 15 ]. Inhibition of G6PD has emerged as a potential therapeutic strategy for cancer treatment, such as the application of the small molecule G6PD inhibitor RRX-001 in colorectal cancer and hepatoma cells [ 16 – 18 ], and the endogenous G6PD inhibitor dehydroepiandrosterone (DHEA: 5-androsten-3beta-ol-17-one) in cervical and breast cancer cells [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these results confirm the rationale for targeting G6PD activity in cancer. Indeed, targeting G6PD with inhibitors has been shown to be a promising strategy for the treatment of cancer [19]. Our results suggest that targeting G6PD with inhibitors in breast cancer patients that have a low level of RIP140 expression might be more efficient.…”
Section: Discussionmentioning
confidence: 75%
“…G6PD regulatory networks are complex in cancer cells, and multiple cis/trans elements regulate G6PD expression. At the transcriptional level, some transcription factors have been described to regulate G6PD expression in various cancers [19]. For instance, NF-κB and pSTAT3 synergistically drive G6PD overexpression and facilitate sensitivity to G6PD inhibition in clear-cell renal cell carcinoma [20].…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant activation of the EMT process accelerates malignancy and drug tolerance of several epithelial carcinomas ( Song et al, 2022 ). EMT progression is regulated by encoding genes, transcription factors, and Circulating exosomes ( Marimuthu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%